You can put this solution on YOUR website!
(-6/y)^3 = (-6)^3/y^3 = -126/y^3
this is because (a/b)^3 = a^3/b^3
let a = 5 and let b = 9
(a/b)^3 = (5/9)^3 = .171467764 (use your calculator to solve)
(a/b)^3 = a^3/b^3 = 5^3/9^3 = 125/729 = .171467764
they are equivalent.
what you were asking me to solve is not an equation, but an expression.
(-6/y)^3 is an expression.
when you make it equal to something, then the whole thing becomes an equation.
(-6/y)^3 = 99635
now you have an equation.
the expression on the left side of the equal sign equals the expression on the right side of the equal sign.